Efficacy and outcome of autologous transplantation in rare myelomas - Morris, Curly; Drake, Mary; Apperley, Jane; Iacobelli, Simona; Biezen, Anja van; Bjorkstrand, Bo; Goldschmidt, Hartmut; Harousseau, Jean-Luc; Morgan, Gareth; Witte, Theo de; Niederwieser, Dietger; Gahrton, Gosta (Haematologica, the hematology journal, 2010)
Background As rare myelomas, i.e. the IgD, IgE, IgM and non-secretory forms, constitute only a small proportion of any study, relatively little is known about their prognosis in the era of peripheral stem cell transplantation.Design and Methods We used the European Group for Blood and Marrow Transplantation Myeloma Database to compare the outcome following autologous transplantation of over 20,000 patients with common myelomas (IgG, IgA and light chain myeloma) with the outcome of patients with rare myelomas: 379 IgD, 13 IgE, 72 IgM and 976 non-secretory cases.Results The study confirms the multiple adverse prognostic factors seen in IgD myeloma. Somewhat surprisingly, patients with IgD and non-secretory myeloma both had higher complete remission rates before and after transplantation than patients with common myelomas. However, while the overall survival of patients with non-secretory myeloma was similar to that of the patients with common myelomas, the survival of patients with IgD myeloma was significantly worse (although better than survival rates reported for non-transplanted patients); this was due to higher transplant-related mortality and relapse/progression rates. The post-transplantation survival of patients with IgE or IgM myeloma appears to be very poor.Conclusions This study provides data on the biological features of rare myelomas. The overall survival of patients with IgD, IgE or IgM myeloma is poor following autologous transplantation but substantially better than that reported for patients who were not transplanted.